Active Mobility and Space Syntax in the city of Blumenau/SC - Pereira, Edilson (National Journal of City Management, 2023)
This research addresses aspects related to active mobility and its relationship with space syntax. Active mobility is a preponderant factor in the quality of urban space, since it is about the characteristics and conditions that a place presents for walking. In this context, this research aims to correlate, under the light of Space Syntax, the results obtained in the evaluation of active mobility with the configurational pattern of 4 spatial clippings of the city of Blumenau/SC. Through the evaluation results that identified active mobility indexes for each area, and the angle analysis of metric integration, in radius of 500, 1000 and 1500 meters, if you can concluded that the active mobility indexes in the researched areas present better results in the areas where the configurational pattern is more integrated, in detriment of the segregated ones.